MENINGKATKAN KEMANDIRIAN BELAJAR PENDIDIKAN AGAMA ISLAM MELALUI PENDEKATAN DIFERENSIASI - Nella Nofrita (Adiba Aisha Amira, 2024)
This research aims to increase student learning independence through implementing a differentiation approach in Islamic Religious Education (PAI) learning in class 4 at SDN 13 Muaro. This research uses a Classroom Action Research (PTK) design with three cycles. Each cycle consists of planning, implementation, observation, and reflection. The research subjects were 29 grade 4 students. Data was collected through observation, interviews and documentation, then analyzed qualitatively and quantitatively. The research results show an increase in student learning independence from low to very high categories through content, process and product differentiation strategies. In conclusion, the differentiation approach is effective in increasing student learning independence.